Robert Singleton will - Singleton, Robert, active 1724-1725.
Will of a resident of Gloucester County, Va.
Handwritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Wills -- Virginia -- Gloucester County; Virginia -- History -- Colonial period, ca. 1600-1775.